Exposure Elements in Disaster Databases and Availability for Local Scale Application: Case Study of Kuala Lumpur, Malaysia - Muhamad, Nurfashareena; Arshad, Siti Hasniza M.; Pereira, Joy Jacqueline (Frontiers in Earth Science, 2021)
Exposure elements in open-access disaster databases that are relevant to critical infrastructure and basic services in the Sendai Framework on Disaster Risk Reduction (SFDRR) were transformed into spatial data, to investigate the impact of flash flood hazards in Kuala Lumpur, Malaysia. In this era of big data and hyper-connectivity, the availability of open-access data on exposure elements across scales and systems is largely unknown. Information on exposure elements and hazard susceptibility provide important insights to enhance community resilience, to move away from merely managing disasters to managing the risk of disasters, in line with the SFDRR. The case study of Kuala Lumpur enabled an assessment of information availability in existing disaster databases and within the national system, to facilitate informed decision-making. Findings reveal that there are a total of 26 databases on the internet that provide information on disasters and related elements; of which 18 are global, three are regional and four provide information at the national scale. However, only ten databases are open access where the user is able to easily retrieve information while others provide a “view only option”. The coverage of exposure elements in disaster databases is very poor where only five databases carried such information; and it is not useful for local scale application. Thus, information was sought from multiple open data sources within the national system and transformed into spatial data, to develop an exposure element data inventory for the city. There are 509 exposure elements within Kuala Lumpur, covering 33 private and government hospitals and community clinics; 189 public and private schools and institutions higher education; 261 facilities that provide basic services; and 26 features that represent of social and economic aspects. The exposure elements, which is coherent with the SFDRR, benefits decision-making when overlain with existing flood hazard zones and susceptible areas. Moving forward, emerging hazards due to climate change will be evaluated to strengthen informed decision-making and build community resilience in the city. The empowerment of local level research has great potential to advance open sharing of information on disaster and climate risks in the region.